2020
DOI: 10.1371/journal.pcbi.1008315
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging functional annotation to identify genes associated with complex diseases

Abstract: To increase statistical power to identify genes associated with complex traits, a number of transcriptome-wide association study (TWAS) methods have been proposed using gene expression as a mediating trait linking genetic variations and diseases. These methods first predict expression levels based on inferred expression quantitative trait loci (eQTLs) and then identify expression-mediated genetic effects on diseases by associating phenotypes with predicted expression levels. The success of these methods critic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…This study extends AD-related genetic loci identified by prior AD-GWAS studies [ 4 6 , 8 11 ] by providing evidence that some loci ( APOE , TOMM40 , PVRL2 , EXOC3L2 , KAT8 and HLA-DRB5 ) may lead to AD by affecting the gene expression levels in the hippocampus. Among the 24 AD- and hippocampus-related genes identified in this study, previous studies only provide clues for the associations of hippocampal expression of PRSS36 , KAT8 , HLA-DRB5 [ 4 ], TOMM40 [ 20 ], CEACAM19 and PVRL2 [ 21 ] with AD. However, some indirect evidence may support other associations.…”
Section: Discussionmentioning
confidence: 99%
“…This study extends AD-related genetic loci identified by prior AD-GWAS studies [ 4 6 , 8 11 ] by providing evidence that some loci ( APOE , TOMM40 , PVRL2 , EXOC3L2 , KAT8 and HLA-DRB5 ) may lead to AD by affecting the gene expression levels in the hippocampus. Among the 24 AD- and hippocampus-related genes identified in this study, previous studies only provide clues for the associations of hippocampal expression of PRSS36 , KAT8 , HLA-DRB5 [ 4 ], TOMM40 [ 20 ], CEACAM19 and PVRL2 [ 21 ] with AD. However, some indirect evidence may support other associations.…”
Section: Discussionmentioning
confidence: 99%
“…5a ), we found marginal evidence of enriched genetic signals in the fibroblasts of lung tissue (p=7.5e-2). IPF-associated genes identified by T-GEN 37 did not show any significant enrichment in any cell type of lung. Therefore, though neither was significant after Bonferroni correction, both transcriptomic and gene-set based genetic analyses suggest the importance of myofibroblasts and fibroblasts consistent with cWAS.…”
Section: Resultsmentioning
confidence: 76%
“…Moreover, genes associated with Mendelian diseases are likely depleted for common cis-eQTLs 40,[51][52][53][54][55] . Future studies could potentially incorporate methods that use rare eQTLs 53 , trans-eQTLs, and epigenetic information 56 to predict gene expression. Alternatively, they could measure gene expression directly using RNA sequencing, to assess whether expression patterns (whatever their causes) are modifying penetrance of rare variants.…”
Section: Discussionmentioning
confidence: 99%